A highly susceptible hACE2-transgenic mouse model for SARS-CoV-2 research - Liu, Gang; Zhang, Min; Wu, Baolei; Zhang, Cheng; Wang, Yan; Han, Xuelian; Wang, Rongjuan; Li, Li; Wei, Yuwei; Sun, Yali; Cao, Xiangwen; Wang, Yuan; et al. (Frontiers in Microbiology, 2024)
Several animal models have been used to assist the development of vaccines and therapeutics since the COVID-19 outbreak. Due to the lack of binding affinity of mouse angiotensin-converting enzyme II (ACE2) to the S protein of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), increasing the susceptibility of mice to SARS-CoV-2 infection was considered in several ways. Here, we generated a COVID-19 mouse model expressing human ACE2 (hACE2) under the control of the CAG promoter. Overexpression of hACE2 did not pose a significant effect on weight growth. After SARS-CoV-2 inoculation, mice showed obvious viral replication and production of inflammation within 7 days, with a gradual decrease in body weight until death. Virological testing found that the virus can replicate in the respiratory system, small intestine, and brain. Additionally, this mouse model was applied to compare two antibody drug candidates, the anti-RBD antibody (MW06) and the mouse CD24-conjugated anti-RBD antibody (mCD24-MW06). Differences in antiviral effects between these two antibodies can be demonstrated in this mouse model when a challenge dose that invalidates the anti-RBD antibody treatment was used. This study provided a new mouse model for studying SARS-CoV-2 pathogenesis and evaluating potential interventions.